Botulinum Toxin Injection for Masseteric Hypertrophy Using 6 Point Injection Technique – A Case Report. Proposal of a Clinical Technique to Quantify Prognosis - Rathod NN; John RS (Dove Medical Press, 2023)
Neha N Rathod, Rubin S John Department of Oral and Maxillofacial Surgery, Saveetha Dental College and Hospitals, Saveetha Institute of Medical and Technical Sciences (SIMATS), Saveetha University, Chennai, Tamil Nadu, 600077, IndiaCorrespondence: Rubin S John, Department of Oral and Maxillofacial Surgery, Saveetha Dental College and hospitals, Saveetha Institute of Medical and Technical Sciences (SIMATS), Saveetha University, Chennai, Tamil Nadu, 600077, India, Email rubinjohn90@gmail.comIntroduction: Masseter hypertrophy presents as unilateral or bilateral swellings over the ramus and angle of the mandible. It is caused by malocclusion, clenching, TMJ disorders, etc and alters facial symmetry, leading to discomfort and negative cosmetic impact in many patients, making this a popular request for aesthetic and functional correction.Materials and Methods: This case report involves injecting Botulinum toxin into 6 equidistant bulging points on the masseter. Standardized photography and clinical parameters were used to assess facial contour and masseter muscle thickness at baseline and successive follow ups.Results and Discussion: Significant masseteric bulk reduction was observed in subsequent follow ups.Conclusion: The 6-point technique was found to be an effective treatment modality for Botox injection in masseteric hypertrophy. The clinical method to quantify prognosis was easy and economical.Keywords: botulinum, hypertrophy, injection, masseter, toxin